Observational studies in male elite football: A systematic mixed study review - Preciado, M.; Anguera, M. T.; Olarte, M.; Lapresa, D. (Frontiers in Psychology, 2019)
Objective: This systematic mixed study review, focuses on the use of observation methodology in elite men's football matches, which constitutes an innovative approach, that opens up a new panorama of useful and productive research.